1970
DOI: 10.1113/jphysiol.1970.sp009158
|View full text |Cite
|
Sign up to set email alerts
|

On the relationships between membrane potential, calcium transient and tension in single barnacle muscle fibres

Abstract: SUMMARY1. The calcium-sensitive photoprotein aequorin has been used to follow the rapid changes in intracellular calcium concentration that occur during the contraction of single muscle fibres from the barnacle Balanus nubilus, Darwin. 2. The transient change in calcium-mediated light emission (calcium transient) and the changes in membrane potential and tension were recorded simultaneously, thus permitting an examination of the relationships between the chemical, electrical, and mechanical events ofexcitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
126
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(136 citation statements)
references
References 22 publications
10
126
0
Order By: Relevance
“…As shown in Table 1 According to recent views, it is clear that increase in the contractile response relates to the increase of myoplasmic free Ca2+ concentrations, that is, an increase of a Ca release from the Ca-storage site within the cell produces an augmentation of contractions (1)(2)(3)(4)24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1 According to recent views, it is clear that increase in the contractile response relates to the increase of myoplasmic free Ca2+ concentrations, that is, an increase of a Ca release from the Ca-storage site within the cell produces an augmentation of contractions (1)(2)(3)(4)24).…”
Section: Discussionmentioning
confidence: 99%
“…In view of recent studies on the excitation-contraction (E-C) coupling mechanism in the heart and skeletal muscles (1)(2)(3)(4)(5), there are several possible mechanisms underlying the positive inotropic action of cardiac glycosides on the heart muscle. Lee and Klaus (6) and Nayler (7,8) concluded that the inotropic response to the glycosides reflects the effects on E-C coupling, and not the effect on either energy metabolism or the contractile protein.…”
mentioning
confidence: 99%
“…Another notion was that the magnesium displacement rate constant could be much altered by the ionic environment within the muscle cell but this possibility has not so far been examined. In addition, it will be of great interest to employ another indicator within the cell whose response to free calcium changes is well documented, such as aequorin [3,4,7] so that the signal from both the aequorin and TnCDANZ signal can be recorded in addition to the force response.…”
Section: Discussionmentioning
confidence: 99%
“…Single muscle fibres from the barnacle (B. nubilus) were isolated and cannulated [7] and axially microinjected with a stock solution of TnCDANZ (13 mM nominally) in 100 mM KC1 (pH 7.0). The volume injected was 0.4~1, so that after dilution the final intracellular concentration was in the range 50-150/M.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation